Analysing control plane scalability issue of software defined wide area network using simulated annealing technique. (14th September 2020) - Sahoo, Kshira Sagar; Ramasubbareddy, Somula; Balusamy, Balamurugan; Deep, B. Vikram
In Software Defined Networks (SDN), the decoupling of the control logic from the data plane provides numerous advantages. Since its inception, SDN is a subject of a wide range of criticism mainly related to the scalability issues of the control plane. To address these limitations, recent architectures have supported the implementation of multiple controllers. Usage of multiple controllers leads to Controller Placement Problems (CPP) particularly in wide area networks. In most of the placement strategies, authors focused on propagation latency, because it is a critical factor in real networks. In this paper, the placement problem has been formulated on the basis of propagation latency as an optimisation problem, and Simulated Annealing (SA) technique has been used to analyse the problem. Further, we investigate the behaviour of SA with four different neighbouring solutions technique. The effectiveness of the algorithms is carried out on TataNld topology and implemented using MATLAB simulator.